A Case Series of Patients Coinfected With Influenza and COVID-19 - Venu Madhav Konala MD, FACP, CACP; Sreedhar Adapa MD, FACP, FASN; Srikanth Naramala MD, FACR, CCD; Avantika Chenna MD, FASN; Shristi Lamichhane MBBS; Pavani Reddy Garlapati MD; Mamtha Balla MD, MPH; Vijay Gayam MD (SAGE Publishing, 2020)
Coronavirus disease 2019, also called COVID-19, is a global pandemic resulting in significant morbidity and mortality worldwide. In the United States, influenza infection occurs mainly during winter and several factors influence the burden of the disease, including circulating virus characteristics, vaccine effectiveness that season, and the duration of the season. We present a case series of 3 patients with coinfection of COVID-19 and influenza, with 2 of them treated successfully and discharged home. We reviewed the literature of patients coinfected with both viruses and discussed the characteristics, as well as treatment options.